Total knee arthroplasty exhibits satisfactory long-term clinical efficacy in the treatment of hemophilia patients with stiff knees - Liu, Yi; Liu, Yi-fan; Meng, Hong-zheng; Sun, Tao; Gao, Ping; Li, Zhao-zhi; Zhang, Wen-qiang (Frontiers in Surgery, 2023)
Objective This study aimed to (1) determine the long-term clinical efficacy of total knee arthroplasty (TKA) in the treatment of hemophilia patients with stiff knessknees, (2) assess the 5- and 10-year prosthesis survival in hemophilia, and (3) determine whether the severity of preoperative stiffness would affect postoperative clinical outcomes and complication rates. Methods The clinical data of 71 patients (78 knees) with hemophilia and concomitant knee stiffness who had undergone TKA between September 2007 and June 2018 were retrospectively analyzed. All patients were male, their mean age at the time of surgery was 38.4. ± 7.9 years (range: 21–63 years), and the mean follow-up time was 8.7 years. To determine the effect of stiffness severity on clinical outcomes, the participants were categorized into two groups: severe [preoperative range of motion (ROM): <50°, 34 knees] and moderate (preoperative ROM: 50–90°, 44 knees). At preoperative and final follow-up, patients' post-TKA clinical and radiological outcomes, quality of life, complications, and long-term survival were assessed. Results Flexion contracture improved from 23.2 ± 10.8° before surgery to 5.9 ± 7.5° upon final follow-up, the Knee Society Score (KSS) increased from 31.4 ± 12.4 to 74.9 ± 11.5, and the KSS functional score increased from 37.6 ± 9.3 to 81.4 ± 12.8. The mean ROM improved from 54.6 ± 32.6° preoperatively to 80.9 ± 34.5° postoperatively. The 36-Item Short Form Survey physical and mental scores also improved significantly. All these differences were statistically significant before and after surgery (P < 0.001). The following postoperative complications occurred in 10 knees (12.8%): hemarthrosis (n = 3), stiffness (n = 4), superficial infection (n = 1), skin necrosis (n = 1), and periprosthetic infection (n = 2), and revision TKA was performed on two knees. The 5- and 10-year survival rates of the prostheses were 98.5% and 93.7%, respectively. The mean ROM in the severe group increased from 30.7 ± 18.7° preoperatively to 70.5 ± 28.3° postoperatively (p < 0.001). The mean flexion contracture decreased from 27.3 ± 10.8° to 6.4 ± 12.0° (p < 0.001). The mean KSS improved from 27.0 ± 7.8 to 68.3 ± 9.6 (p < 0.001). The mean ROM in the moderate group improved from 84.3 ± 22.7 to 92.9 ± 28.8 (p < 0.001), while the mean flexion contracture decreased from 12.8 ± 11.0° to 4.8 ± 5.0° (p < 0.001) and the mean KSS improved from 41.3 ± 11.5 to 81.3 ± 12.2 (p < 0.001). The severe group had worse postoperative ROM and functional scores than the moderate group. Furthermore, the severe group used varus-valgus constrained or hinged prostheses more frequently (52.8% vs. 18.1%) and had more complications (18.9% vs. 9.0%) than the moderate group. Conclusion TKA exhibits satisfactory long-term efficacy in patients with hemophilic knee joint disease involving preoperative stiffness, thus potentially providing a significant improvement in function and reducing pain. Furthermore, severely stiff knee joints have worse clinical outcomes and more complications than moderately stiff knee joints.